Water Resources Utilization, Conflicts and Interventions in the Tana Basin of Kenya - Agwata, Jones (My University, 2005)
Water is an essential resource necessary for social and economic development of any country. When it is available in sufficient quantities and acceptable quality, it is extensively used for domestic, agricultural and industrial purposes. Some of the uses include drinking; washing, watering of livestock, growing crops and the manufacture of finished goods in industry. In Kenya, adequate water is available only in 20% of the country’s landmass whilst in the rest and biggest portion of the country including the arid and semi-arid lands, it has to be mined from the ground or harvested in dams, and pans. Due to the scarcity of water in the arid and semi-arid regions of the country and its uneven and poor distribution in the high and medium potential areas, its utilization for various functions in any basin often leads to conflicts. These conflicts require appropriate interventions in the form of conservation, protection of water sources and apportionment to meet various water needs in an integrated and sustainable manner. In this paper, a brief overview of the water resources in Kenya is provided and the utilization of water in the Tana Basin and the associated conflicts and interventions examined. The main issues related to water in the basin should be addressed to ensure that the available water is managed in an integrated manner. Also, some of the necessary institutional frameworks for integrated and sustainable water resource management in the basin are proposed.